2016
DOI: 10.3758/s13421-016-0607-x
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of historical memories and social-distance attitudes in post-war second-generation Croatians

Abstract: Intergenerational transmission of memory is a process by which biographical knowledge contributes to the construction of collective memory (representation of a shared past). We investigated the intergenerational transmission of war-related memories and social-distance attitudes in second-generation post-war Croatians. We compared 2 groups of young adults from (1) Eastern Croatia (extensively affected by the war) and (2) Western Croatia (affected relatively less by the war). Participants were asked to (a) recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 45 publications
(57 reference statements)
1
24
0
2
Order By: Relevance
“…We note that there is an extensive qualitative literature on the intergenerational transmission of traumatic memories and war which finds both conflicting and supporting evidence for the idea that knowledge of previous generations' trauma may be related to well‐being. Much of this literature focuses on what happens when narratives are not told, and trauma is silenced (see Danieli, for a review; Tschuggnall & Welzer, ; Svob et al, ). Baker and Gippenreiter (), for example, find positive effects on well‐being for individuals researching one's previously‐silenced intergenerational history of trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that there is an extensive qualitative literature on the intergenerational transmission of traumatic memories and war which finds both conflicting and supporting evidence for the idea that knowledge of previous generations' trauma may be related to well‐being. Much of this literature focuses on what happens when narratives are not told, and trauma is silenced (see Danieli, for a review; Tschuggnall & Welzer, ; Svob et al, ). Baker and Gippenreiter (), for example, find positive effects on well‐being for individuals researching one's previously‐silenced intergenerational history of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Intergenerational narratives provide implicit and explicit frameworks by modeling gender and cultural norms of storytelling, and more explicitly sharing values and how to understand human behavior (Pratt, Norris, Hebblethwaite, & Arnold, ; Ryan, Pearce, Anas, & Norris, ; Svob, Brown, Takšić, Katulić, & Žauhar, ; Zaman & Fivush, ). Family storytelling occurs multiple times within families' daily conversations, strengthening bonds among members and reinforcing family values and identity from as early as children's infancy (Bohanek et al, ; Fiese, Hooker, Kotary, Schwagler, & Rimmer, ; Koenig Kellas, ; Pratt & Fiese, ).…”
Section: Intergenerational Narratives and Gendermentioning
confidence: 99%
“…Presently, there are discussions about the impact of historical events such as colonization, slavery and displacement trauma in many cultures, including First Nations and native American communities, African Americans, Australian aboriginals and New Zealand Maori, as well as in societies exposed to genocide, ethnic cleansing or war, such as Cambodians, Armenians, Rwandans, Palestinians, and communities in the former Yugoslavia. There is also a growing literature about offspring effects following early maternal childhood maltreatment.…”
Section: The Origin Of Studies Of Intergenerational Trauma Effectsmentioning
confidence: 99%
“…In a study published last year 8 , they reported that the children of Croatians who had lived through the Yugoslav wars of the 1990s were more likely to recall their parents' war-related experiences -getting shot, for example, or the house being bombed -than their non-war-related ones, such as marriage or birth of a first child. Wars, like immigration, bring great upheaval in their wake, and so are highly memorable, says Svob. This 'transition theory' she says, could also explain one of the biggest voids in Westerners' collective memory of the twentieth century -why they easily recall the two world wars, but not the Spanish flu pandemic of 1918-20 that probably killed more than either of them.…”
Section: Making Memories Making Historiesmentioning
confidence: 99%